Profitable Sarbanes-Oxley compliance : - Northrup, C. Lynn (J. Ross Pub, 2006)
The Sarbanes-Oxley Act is here to stay. This unique reference not only shows how to achieve compliance with Sarbanes-Oxley, but also guides senior executives and their management teams in assessing the reliability of financial reporting and internal controls to maintain compliance. Unlike other SOX books, it shows how to use the process to reduce risks and improve profitability, shareholder value and operational performance.